The Influence of Tax Rates and Tax Sanctions on Taxpayers Tax Receipts at the Medan Timur Pratama Service Office - Alvin Jessen (Outline Journal of Management and Accounting, 2022)
This study aims to determine the effect of tax rates and tax sanctions on taxpayers tax receipts at the Pratama Medan Timur Tax Service Office. The type of data used in this research is quantitative data, which is obtained in the form of numbers and numbers. Source of data in the form of primary data. The population in this study is the Tax Office Pratama Medan Timur as many as 46.902 people. From the population, selected by incidental sampling technique and obtained as many as 100 respondents. The results of the research analysis show that the tax rate has a significant effect on taxpayers tax receipts at the Pratama Medan Timur Tax Service Office. The results of the research analysis show that tax sanctions have a significant effect on taxpayers tax receipts at the Pratama Medan Timur Tax Service Office. The results of the research analysis show that tax rates and tax sanctions have a significant effect on taxpayers tax receipts at the Pratama Medan Timur Tax Service Office. Coefficient of determination (R Square) of 0.453 or 45.3% which means that the variable of Tax Revenue can be explained by the variable Effect of Tax Rates and Tax Sanctions of 45.3% and the remaining 54.7% is explained by other variables.